PENGARUH KECERDASAN EMOSIONAL, PROFESIONALISME KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN PDAM TIRTA MAHOTTAMA KABUPATEN KLUNGKUNG - I Ketut Rahmatika; Anak Agung Putu Agung; Ni Putu Nita Anggraini (EMAS, 2022)
The purpose of this study was to examine and obtain empirical evidence of the effect of emotional intelligence, work professionalism and commitment on employee performance. The population in this study were all employees of PDAM Tirta Mahottama, Klungkung Regency, amounting to 136 people. The sample in this study was 58 respondents determined by the Slovin formula. The sample selection used in this study is by means of probability, the probability technique used is proportionate stratifield random sampling. The data analysis technique used is multiple linear regression. The results showed that emotional intelligence, work professionalism and commitment had a positive and significant effect on employee performance.